2007
DOI: 10.1017/s0954579407070113
|View full text |Cite
|
Sign up to set email alerts
|

Maternal drug abuse versus maternal depression: Vulnerability and resilience among school-age and adolescent offspring

Abstract: In this study of 360 low-income mother-child dyads, our primary goal was to disentangle risks linked with commonly co-occurring maternal diagnoses: substance abuse and affective/anxiety disorders. Variable-and person-based analyses suggest that, at least through children's early adolescence, maternal drug use is no more inimical for them than is maternal depression. A second goal was to illuminate vulnerability and protective processes linked with mothers' everyday functioning, and results showed that negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 47 publications
3
75
0
Order By: Relevance
“…In general, there is a need for more studies examining within-group differences in high-risk children to replicate and expand upon findings from previous such studies (Cicchetti and Rogosch 1997;GormanSmith et al 2004;Luthar and Sexton 2007;VanderbiltAdriance and Shaw in press). Relating back to a narrower conceptualization of resilience, researchers should clearly specify the particular outcome in question, and discuss their results as specific to that outcome, instead of referring to a general, overall ''resilient'' outcome.…”
Section: Future Directionsmentioning
confidence: 95%
See 4 more Smart Citations
“…In general, there is a need for more studies examining within-group differences in high-risk children to replicate and expand upon findings from previous such studies (Cicchetti and Rogosch 1997;GormanSmith et al 2004;Luthar and Sexton 2007;VanderbiltAdriance and Shaw in press). Relating back to a narrower conceptualization of resilience, researchers should clearly specify the particular outcome in question, and discuss their results as specific to that outcome, instead of referring to a general, overall ''resilient'' outcome.…”
Section: Future Directionsmentioning
confidence: 95%
“…Other samples of predominantly low-income, ethnically diverse samples also show a high rate of problems among at-risk children (Buckner et al 2003;Luthar and Sexton 2007;Stouthamer-Loeber et al 2004). For example, a study of low-income children of mothers with psychiatric diagnoses found that only 7-21% of the children displayed positive outcomes (i.e., average levels of social competence and low externalizing or internalizing symptoms; Luthar and Sexton 2007).…”
Section: Higher Risk Contexts: Multiple Risk Factors and Impoverishedmentioning
confidence: 99%
See 3 more Smart Citations